2020
DOI: 10.1029/2020gl090888
|View full text |Cite
|
Sign up to set email alerts
|

Do Surface Temperature Indices Reflect Centennial‐Timescale Trends in Atlantic Meridional Overturning Circulation Strength?

Abstract: The difference between North Atlantic subpolar gyre sea surface temperatures (SPG SSTs) and hemispheric-or global-scale surface temperatures has been utilized as an index of centennial-timescale changes in Atlantic Meridional Overturning Circulation (AMOC) strength. Here, using Community Earth System Model ensembles, we show that surface temperature-based indices (STIs) proposed to date largely reflect global-scale temperature trends and thus do not reflect dynamical relationships with AMOC. More broadly, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Indeed, a proxy for AMOC strength using the difference between 'warming hole' SSTs and global mean SSTs 25,123 suggests an AMOC weakening of 3 ± 1 Sv since the middle of the twentieth century. However, the interpretation of this proxy for changes in the AMOC 10,119,164,165 and its Stippling indicates statistically significant trends (P < 0.05). Analysis and regions adapted from ref.…”
Section: Linking To the Pastmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, a proxy for AMOC strength using the difference between 'warming hole' SSTs and global mean SSTs 25,123 suggests an AMOC weakening of 3 ± 1 Sv since the middle of the twentieth century. However, the interpretation of this proxy for changes in the AMOC 10,119,164,165 and its Stippling indicates statistically significant trends (P < 0.05). Analysis and regions adapted from ref.…”
Section: Linking To the Pastmentioning
confidence: 92%
“…applicability to the historical period 10,165 have substantial uncertainties. Although it has been suggested that this weakening is the result of fresh water from melting glaciers 123 (which climate models represent poorly or not at all), such impacts are not yet considered to be large enough to influence the AMOC 166,167 .…”
Section: ();mentioning
confidence: 99%
See 1 more Smart Citation
“…The decline occurred in a sharp reduction in early 2009 and not in a gradual, steady decline suggested by proxy time series. The proxies are often based on sea surface temperature records in the Atlantic and observed temperature changes may be related to global warming rather than changes in the AMOC [62]. In the subpolar gyre where temperature (and salinity) has steadily declined as a result of the reduced AMOC since 2009 [56], proxies based on surface temperature may capture accumulating effects of a change in the AMOC, but they do not reflect the sharp reduction in the strength of the AMOC.…”
Section: Is the Atlantic Meridional Overturning Circulation Declining?mentioning
confidence: 99%
“…Several studies have suggested that some of the dramatic hydrographic changes seen in the western North Atlantic near the Gulf of Maine, particularly the warming in the Gulf of St. Lawrence 12 and the decrease in nitrogen isotopes outside of the Gulf of Maine 25 , have been caused by a significant weakening of the AMOC over the last 50-150 years 25,61,62 . However, a weakened AMOC in the 21st century is still debated 63,64 , particularly as there are many other proxy records that do not suggest a recent weakening of the AMOC 16 .…”
Section: Discussionmentioning
confidence: 99%